Preparation method and application of composite catalyst for iron-chromium flow battery electrode

By carbonizing the tea residue and combining it with sodium tungstate, a composite catalyst for iron-chromium flow batteries was prepared, which solved the problems of poor conductivity, poor hydrophilicity and low capacity retention of the carbon cloth material, and significantly improved the electrochemical performance of the battery electrode.

CN119560571AActive Publication Date: 2025-03-04ZHONGHAI ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411416866.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-04
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing carbon cloth materials have problems such as poor conductivity, poor hydrophilicity and low capacity retention in iron-chromium flow batteries, which are difficult to meet the high performance needs of battery electrodes.

Method used

The tea residue was pretreated and carbonized, combined with sodium tungstate for ultrasonic mixing, and treated by hydrothermal method. Finally, after drying, calcining and washing, a composite catalyst was prepared to improve the hydrophilicity and electrical conductivity of the carbon cloth.

Benefits of technology

The composite catalyst significantly improves the hydrophilicity and conductivity of the carbon cloth, enhances the capacity retention rate of the battery electrode, promotes the improvement of electrochemical performance, and can increase the capacity retention rate by 50% after 60 charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560571A_ABST
    Figure CN119560571A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy materials, and particularly discloses a preparation method and application of a composite catalyst for an iron-chromium flow battery electrode, tea residues are used as raw materials, a biochar precursor is obtained through a series of treatment, then the biochar precursor and sodium tungstate are subjected to ultrasonic mixing, then a hydrothermal method is adopted, and the composite catalyst for the iron-chromium flow battery electrode is obtained. And drying, roasting, washing and the like to obtain the composite catalyst. The composite catalyst which can be applied to the negative electrode carbon cloth of the iron-chromium flow battery is prepared by taking the organic solid waste as a base and combining the carbonized organic solid waste with sodium tungstate capable of promoting the improvement of the battery performance by utilizing the characteristic that the carbonized organic solid waste has a developed pore structure. When the catalyst is applied to a carbon cloth electrode of an iron-chromium flow battery, the hydrophilicity and conductivity of the carbon cloth can be well improved, the capacity retention ratio of the carbon cloth can be increased, and the improvement of the electrochemical performance of the battery is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy materials, and in particular to a preparation method and application of a composite catalyst for an iron-chromium liquid flow battery electrode. Background Art

[0002] Electrochemical energy storage requires a more flexible technical supplement. Lithium-ion batteries are the main form of electrochemical energy storage, but they have some technical bottlenecks, such as poor safety and short cycle life. Therefore, it is necessary to seek a safer, more reliable and durable energy storage technology to meet the energy storage needs brought about by the rapid development of renewable energy.

[0003] Liquid flow batteries have many advantages such as low cost, large scale, and strong safety, and are considered to be one of the preferred technologies for large-scale energy storage technology. Iron-chromium liquid flow batteries have many advantages such as green safety, low toxicity and low corrosion, a relatively large operating temperature range, abundant electrolyte raw material resources, and low price. At present, the research and development progress is relatively fast, and it is expected to become one of the mainstream routes of liquid flow batteries in the future.

[0004] As a key material for flow batteries, electrodes should have good corrosion resistance, excellent electrochemical activity and stability. Carbon cloth is a highly flexible and conductive material that has been used in fuel cells and supercapacitors. In flow batteries, carbon cloth is also an excellent electrode material, but currently unmodified carbon cloth has problems such as poor conductivity, poor hydrophilicity, and low capacity retention. Therefore, there is an urgent need for a catalyst that can act on iron-chromium flow batteries to improve the battery's electrode performance. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a preparation method and application of a composite catalyst for iron-chromium liquid flow battery electrodes. Tea residue is used as raw material, and a biochar precursor is obtained through a series of treatments. The biochar precursor is then ultrasonically mixed with sodium tungstate, and then a hydrothermal method is used. After drying, roasting, washing and other operations, a composite catalyst is obtained. The catalyst can greatly improve the hydrophilicity and conductivity of carbon cloth, and can improve the capacity retention rate of carbon cloth, thereby promoting the improvement of the electrochemical performance of the battery and solving the problems mentioned in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, comprising the following steps:

[0007] S1. Pretreatment of biomass waste: The collected biomass waste is washed with deionized water, dried and crushed, and then placed in a muffle furnace for pre-carbonization, and then acid-washed to obtain a biochar precursor;

[0008] S2. preparing a tungsten salt aqueous solution: preparing a tungsten salt aqueous solution by ultrasonic treatment;

[0009] S3, hydrothermal reaction: immersing the biochar precursor in a tungsten salt aqueous solution, adding an oxalic acid solution, and then ultrasonically treating the mixture, and subjecting the mixture to a hydrothermal reaction;

[0010] S4. After drying, calcining and washing, a composite catalyst is obtained: after the hydrothermal reaction is completed, the mixture is placed in an oven to dry, and then the mixture is calcined under nitrogen protection, the calcined sample is washed with deionized water until it is neutral, and the composite catalyst is obtained after drying.

[0011] Preferably, in step S1, the biomass waste is tea residue, which is crushed and then passed through a 100-mesh sieve.

[0012] Preferably, in step S1, the pre-carbonization temperature is 600°C and the pre-carbonization time is 30 minutes.

[0013] Preferably, in step S1, the acid used for pickling is dilute hydrochloric acid with a concentration of 0.1 mol / L.

[0014] Preferably, in step S2, the tungsten salt is Na 2 WO 4 ·2H 2 O, the mass ratio of tungsten salt to water is 9.8955:100, the ultrasonic treatment time is 10 min, and the concentration of the tungsten salt aqueous solution is 0.3 mol / L.

[0015] Preferably, in step S3, the molar ratio of the oxalic acid solution to the tungsten salt aqueous solution is 1:1; the ultrasonic treatment time is 10 min; the temperature of the hydrothermal reaction is 180° C., and the time is 24 h.

[0016] Preferably, in step S4, the calcination temperature is 800° C. and the holding time is 2 h.

[0017] On the other hand, to achieve the above-mentioned purpose, the present invention also provides the following technical solution: application of a composite catalyst in a carbon cloth electrode of an iron-chromium liquid flow battery.

[0018] Preferably, the application specifically includes the following:

[0019] The purchased carbon cloth was pretreated, washed with deionized water after cutting, and then placed in a muffle furnace for high-temperature activation;

[0020] The composite catalyst is mixed with the adhesive, and the catalyst ink is obtained after ultrasonic treatment, and the pretreated carbon is then arranged therein, and dried after standing;

[0021] The process is repeated several times until the ink is completely absorbed to obtain a carbon cloth electrode modified with a composite catalyst.

[0022] Preferably, the size of the carbon cloth is 540 mm×200 mm; the temperature of the high-temperature activation is 500° C., and the time is 2 hours.

[0023] The beneficial effects of the present invention are as follows: the present invention is based on organic solid waste, and utilizes the characteristics of the developed pore structure after carbonization, and combines it with sodium tungstate that can promote the improvement of battery performance, to prepare a composite catalyst that can be applied to the negative electrode carbon cloth of the iron-chromium liquid flow battery. The catalyst is applied to the carbon cloth electrode of the iron-chromium liquid flow battery, which can greatly improve the hydrophilicity and conductivity of the carbon cloth, and can improve the capacity retention rate of the carbon cloth, thereby promoting the improvement of the electrochemical performance of the battery. In the liquid flow battery where the electrolyte is constantly flowing, the electrochemical performance of the electrode is stable. After 60 charge and discharge cycles, the capacity retention rate is 50% higher than that of the original carbon cloth, and has a good capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a scanning electron microscope photo of unmodified carbon cloth;

[0025] Figure 2 Schematic diagram of the contact angle of unmodified carbon cloth;

[0026] Figure 3 This is a schematic diagram of the contact angle of the carbon cloth in Example 1;

[0027] Figure 4 This is a schematic diagram of the contact angle of the carbon cloth in Example 4;

[0028] Figure 5 This is a schematic diagram of the contact angle of the carbon cloth in Example 5;

[0029] Figure 6 This is the battery capacity retention rate curve of Example 4. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention provides a technical solution: a method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, which specifically includes the following:

[0032] S1. Pretreatment of biomass waste: The collected biomass waste (tea residue) was washed with deionized water, dried and crushed (passed through a 100-mesh sieve after crushing), and placed in a muffle furnace for pre-carbonization at a temperature of 600°C for 30 minutes. The pre-carbonization temperature was then acid washed (dilute hydrochloric acid, concentration of 0.1 mol / L) to obtain a biochar precursor;

[0033] S2. preparing a tungsten salt aqueous solution: preparing a tungsten salt aqueous solution by ultrasonic treatment;

[0034] The tungsten salt is Na 2 WO 4 ·2H 2 O, the mass ratio of tungsten salt to water is 9.8955 or 6.597 or 13.194:100, the ultrasonic treatment time is 10 min, and the concentration of the tungsten salt aqueous solution is 0.2-0.4 mol / L.

[0035] S3, hydrothermal reaction: immerse the biochar precursor in a tungsten salt aqueous solution, add oxalic acid solution, and then ultrasonicate for 10 minutes. Pour the ultrasonicated mixture into a reactor, and then transfer it to an oven, and finally perform a hydrothermal reaction at a temperature of 180°C for 24 hours.

[0036] The molar ratio of the oxalic acid solution to the tungsten salt aqueous solution is 1:1.

[0037] S4. After drying, calcining and washing, a composite catalyst is obtained: after the hydrothermal reaction is completed, the mixture is placed in an oven for drying, and then the mixture is placed in a tubular furnace and calcined under nitrogen protection. The calcination temperature is 600-800°C and the holding time is 2-4h. The calcined sample is washed with deionized water until it is neutral, and the composite catalyst is obtained after drying.

[0038] The application of the composite catalyst prepared by the above preparation method in the carbon cloth electrode of the iron-chromium liquid flow battery specifically includes the following:

[0039] The purchased carbon cloth was pretreated, washed with deionized water after cutting, and then placed in a muffle furnace for high-temperature activation; the carbon cloth was a commercially available PAN-based carbon cloth with a thickness of 0.167 mm and a size of 540 mm×200 mm; the high-temperature activation temperature was 500° C. and the time was 2 h;

[0040] The composite catalyst is mixed with the adhesive, and the catalyst ink is obtained after ultrasonic treatment, and the pretreated carbon is then arranged therein, and dried after standing;

[0041] The process is repeated several times until the ink is completely absorbed to obtain a carbon cloth electrode modified with a composite catalyst.

[0042] Furthermore, the binder is N,N-dimethylformamide (DMF); the mass volume ratio of the composite catalyst to N,N-dimethylformamide (DMF) is 1 mg:2.2 ml.

[0043] The commercially available carbon cloth was used to assemble a single cell with an electrode area of ​​540 mm × 200 mm. The microscopic photograph of the commercially available unmodified carbon cloth is shown in Figure 1 As shown, its hydrophilicity is Figure 2 As shown, the supporting electrolyte is a 2 mol / L HCl solution, the iron ion concentration in the electrolyte is 1.2 mol / L, and the chromium ion concentration is 1.4 mol / L.

[0044] Example 1

[0045] A method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, specifically comprising the following steps:

[0046] S1. Pretreatment of biomass waste: The collected biomass waste (tea residue) was washed with deionized water, dried and crushed (passed through a 100-mesh sieve after crushing), and placed in a muffle furnace for pre-carbonization at a temperature of 600°C for 30 minutes. The pre-carbonization temperature was then acid washed (dilute hydrochloric acid, concentration of 0.1 mol / L) to obtain a biochar precursor;

[0047] S2. preparing a tungsten salt aqueous solution: preparing a tungsten salt aqueous solution by ultrasonic treatment;

[0048] The tungsten salt is Na 2 WO 4 ·2H 2 O, the mass ratio of tungsten salt to water is 6.597:100, the ultrasonic treatment time is 10 min, and the concentration of the tungsten salt aqueous solution is 0.2 mol / L.

[0049] S3, hydrothermal reaction: immerse the biochar precursor in a tungsten salt aqueous solution, add oxalic acid solution, and then ultrasonicate for 10 minutes. Pour the ultrasonicated mixture into a reactor, and then transfer it to an oven, and finally perform a hydrothermal reaction at a temperature of 180°C for 24 hours.

[0050] The molar ratio of the oxalic acid solution to the tungsten salt aqueous solution is 1:1.

[0051] S4. After drying, calcining and washing, a composite catalyst is obtained: after the hydrothermal reaction is completed, the mixture is placed in an oven for drying, and then the mixture is placed in a tubular furnace and calcined under nitrogen protection. The calcination temperature is 800°C and the holding time is 2h. The calcined sample is washed with deionized water until it is neutral, and the composite catalyst is obtained after drying.

[0052] Example 2

[0053] A method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, wherein the steps are basically the same as those of Example 1, except that the calcination time in step S4 is 3 hours.

[0054] Example 3

[0055] A method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, wherein the steps are basically the same as those of Example 1, except that the calcination time in step S4 is 4 hours.

[0056] Comparing the results of Examples 1-3, the preferred calcination time is 2 h. After the composite catalyst is loaded onto the carbon cloth, the hydrophilicity is improved. Figure 3 shown.

[0057] Example 4

[0058] A method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, the steps are basically the same as those in Example 1, except that step S2 is carried out according to Na 2 WO 4 ·2H 2 O: water mass ratio of 9.8955:100 to prepare 0.3 mol / L tungsten salt aqueous solution. The use of the composite catalyst can significantly improve the hydrophilicity of carbon cloth, such as Figure 4 shown.

[0059] Example 5

[0060] A method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, the steps are basically the same as those in Example 1, except that step S2 is carried out according to Na 2 WO 4 ·2H 2 The mass ratio of O: water is 13.194:100 to obtain a 0.4 mol / L tungsten salt aqueous solution. The use of the composite catalyst also significantly improves the hydrophilicity of the carbon cloth, such as Figure 5 shown.

[0061] Comparing the results of Example 1 to Example 5, the preferred ratio of the tungsten salt aqueous solution is Na 2 WO 4 ·2H 2 O: water mass ratio of 9.8955:100 to obtain 0.3 mol / L tungsten salt aqueous solution. Thus, it is combined with tea residue biochar to obtain a composite catalyst. The hydrophilicity of the carbon cloth electrode loaded with the composite catalyst is improved, and after 60 cycles of the battery, the battery capacity retention rate curve is as follows Figure 6 As shown, the battery capacity decays slower than that of the battery without catalyst loading and is 50% higher than that of the battery without catalyst loading.

[0062] The present invention uses organic solid waste as a base, utilizes its characteristic of having a developed pore structure after carbonization, and combines it with sodium tungstate that can promote the improvement of battery performance to prepare a composite catalyst that can be applied to the negative electrode carbon cloth of the iron-chromium liquid flow battery. The catalyst is applied to the carbon cloth electrode of the iron-chromium liquid flow battery, which can greatly improve the hydrophilicity and conductivity of the carbon cloth, and can improve the capacity retention rate of the carbon cloth, thereby promoting the improvement of the electrochemical performance of the battery.

[0063] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0064] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode, characterized in that: The steps include: S1. Pretreatment of biomass waste: The collected biomass waste is washed with deionized water, dried and crushed, and then placed in a muffle furnace for pre-carbonization, and then acid-washed to obtain a biochar precursor; S2. preparing a tungsten salt aqueous solution: preparing a tungsten salt aqueous solution by ultrasonic treatment; S3, hydrothermal reaction: immersing the biochar precursor in a tungsten salt aqueous solution, adding an oxalic acid solution, and then ultrasonically treating the mixture, and subjecting the mixture to a hydrothermal reaction; S4. After drying, calcining and washing, a composite catalyst is obtained: after the hydrothermal reaction is completed, the mixture is placed in an oven to dry, and then the mixture is calcined under nitrogen protection, the calcined sample is washed with deionized water until it is neutral, and the composite catalyst is obtained after drying.

2. The method for preparing a composite catalyst for an iron-chromium flow battery electrode according to claim 1, characterized in that: In step S1, the biomass waste is tea residue, which is crushed and passed through a 100-mesh sieve.

3. The method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode according to claim 1, characterized in that: In step S1, the pre-carbonization temperature is 600°C and the pre-carbonization time is 30 minutes.

4. The method for preparing a composite catalyst for an iron-chromium liquid flow battery electrode according to claim 1, characterized in that: In step S1, the acid used for pickling is dilute hydrochloric acid with a concentration of 0.1 mol / L.

5. The method for preparing the composite catalyst for iron-chromium redox flow battery electrode according to claim 1, characterized in that: In step S2, the tungsten salt is Na2WO4·2H2O, the mass ratio of the tungsten salt to water is 9.8955:100, the ultrasonic treatment time is 10 min, and the concentration of the tungsten salt aqueous solution is 0.3 mol / L.

6. The method for preparing the composite catalyst for iron-chromium liquid flow battery electrode according to claim 1, characterized in that: In step S3, the molar ratio of the oxalic acid solution to the tungsten salt aqueous solution is 1:1; the ultrasonic treatment time is 10 minutes; the temperature of the hydrothermal reaction is 180° C., and the time is 24 hours.

7. The method for preparing a composite catalyst for an iron-chromium redox flow battery electrode according to claim 1, characterized in that: In step S4, the calcination temperature is 800° C. and the holding time is 2 hours.

8. Use of the composite catalyst prepared by the preparation method according to any one of claims 1 to 7 in a carbon cloth electrode of an iron-chromium liquid flow battery.

9. The use according to claim 8, characterized in that: The details include: The purchased carbon cloth was pretreated, washed with deionized water after cutting, and then placed in a muffle furnace for high-temperature activation; The composite catalyst is mixed with the adhesive, and the catalyst ink is obtained after ultrasonic treatment, and the pretreated carbon is then arranged therein, and dried after standing; The process is repeated several times until the ink is completely absorbed to obtain a carbon cloth electrode modified with a composite catalyst.

10. The use according to claim 9, characterized in that: The carbon cloth has a size of 540 mm×200 mm; the high temperature activation temperature is 500° C. and the time is 2 h.

Citation Information

Patent Citations

  • Bromine electrode for bromine hydride energy storage battery and preparation method of bromine electrode

    CN105702977A

  • Biomass charcoal-bicrystal phase metal oxide (WO3) composite material, and preparation and application thereof

    CN111474211A

  • Preparation and application of biomass charcoal in-situ growth cobalt and cobalt tungsten oxide composite catalyst

    CN116832821A

  • Electrode, battery cell, and redox flow battery

    WO2022209113A1